2005
DOI: 10.1002/uog.2029
|View full text |Cite
|
Sign up to set email alerts
|

OC6.02: Growth rate of corpus callosum in very premature infants

Abstract: Objective: A bedside method for assessing the effectiveness of strategies to improve cerebral development in very premature infants is desirable. The aim of this study was to compare the growth trajectory of the corpus callosum on cranial ultrasound in very premature infants and compare it with the growth rate seen antenatally. Methods: We recruited 100 very low birth weight infants admitted to a single regional Level III neonatal intensive care unit from November 1998 to November 2000. Sixty-four (32 boys) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 0 publications
3
41
0
1
Order By: Relevance
“…27 In accordance with previous studies, we showed satisfactory reproducibility for CC length. 7 CCF reproducibility was excellent too; this finding suggests that both measurements are feasible for longitudinal evaluation of brain growth. Increasing lengths with increasing ages and weights, as shown in the growth charts, support the use of these markers in clinical practice.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…27 In accordance with previous studies, we showed satisfactory reproducibility for CC length. 7 CCF reproducibility was excellent too; this finding suggests that both measurements are feasible for longitudinal evaluation of brain growth. Increasing lengths with increasing ages and weights, as shown in the growth charts, support the use of these markers in clinical practice.…”
Section: Discussionmentioning
confidence: 68%
“…[7][8][9][10] One explanation for this is that the brain has few easily recognizable and consistent landmarks for reliable measurements on CUS. The CC, a flat bundle of white matter that connects the left and right hemispheres, is one of the brain structures that is easily visualized and recognizable on CUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 In addition, in sonography studies regarding very premature infants, the length of the corpus callosum at term equivalency was significantly shorter than that in control infants, and the growth rate of corpus callosal length has significant correlation with clinical outcome. 15,16 We then consider that the length of the corpus callosum, as well as its size and shape, reflects the volume of the myelinated white matter. Consequently, the significant correlation between whole pontine diameter and corpus callosal length may reflect the volume of the cerebral myelinated white matter.…”
Section: Discussionmentioning
confidence: 99%
“…It will reach an adult appearance by approximately 9 to 10 months of age [44]. One should also be aware that growth of the corpus callosum is typically slower in premature infants compared to infants of the same gestational age [45].…”
Section: Corpus Callosum: More Than Just Another Midline Structure Wmentioning
confidence: 99%